Candidate SNP markers of social dominance, which may affect the affinity of the TATAbinding protein for human gene promoters - I. V. Chadaeva; D. A. Rasskazov; E. B. Sharypova; L. K. Savinkova; P. M. Ponomarenko; M. P. Ponomarenko (Вавиловский журнал генетики и селекции, 2017)
The following heuristic hypothesis has been proposed: if an excess of a protein in several animal organs was experimentally identified as physiological marker of increased aggressiveness and if a polymorphism (SNP) can cause superexpression of the human gene homologous of the animal gene encoding this protein, then this polymorphism can be a candidate SNP marker of social dominance, whereas a deficient expression corresponds to subordinate and vice versa. Within this hypothesis, we analyzed 21 human genes –ADORA2A, BDNF, CC2D1A, CC2D1B, ESR2, FEV, FOS, GH1, GLTSCR2, GRIN1, HTR1B, HTR1A, HTR2A, HTR2C, LGI4, LEP, MAOA, SLC17A7, SLC6A3, SNCA, TH – which represent the functions of proteins known as physiological markers of aggressive behavior in animals: hormones and their receptors, biosynthetic enzymes and receptors of neurotransmitters, transcription and neurotrophic factors. These proteins may play an important role in determining hierarchical relationships in social animals. Using our previously developed Web-service SNP_TATA_Comparator (http://beehive.bionet.nsc.ru/cgi-bin/mgs/tatascan/start.pl), we analyzed 381 SNPs within the region of [–70; –20] relative to the start protein-coding transcripts, which is the region of the all known TATA-binding protein (TBP) binding sites. We took them from the database dbSNP, v.147 As a result, we found 45 and 47 candidate SNP markers of dominance and submission, respectively (e. g., rs373600960 and rs747572588). Within the framework of the proposed heuristic hypotheses and database dbSNP v.147, we found statistically significant (α < 10-5) evidence of the effects of natural selection against the deficient expression of genes, which can affect the predisposition to dominate, as well as in favor of both subordination and domination behavior as a norm of reaction of aggressiveness (difference not significant: α > 0.35). The proposed hypothesis, the candidate SNP markers predicted and the observed regularities of effects of natural selection for the human genome are discussed in comparison with published data: whether they can have any relation to social dominance in human. It was concluded that these results require experimental verification.